NOG1 increases grain production in rice - Xing Huo (Nature Portfolio, 2017)
Rice grain yield is a quantitative trait determined by multiple genes. Here, the authors find NOG1, which encodes an enoyl-CoA hydratase/isomerase in fatty acid β-oxidation pathway, can increase grain yield by enhancing grain number per panicle without affecting the other yield component traits.